Observer Output Feedback Load Frequency Control for a Two-Area Interconnected Power System - Van Van Huynh; Hoang-Duy Vo; Bui Le Ngoc Minh; Tam Minh Nguyen; Yao Wen Tai (Journal of Advanced Engineering and Computation, 2018)
Most of existing results for load frequency control is achieved under assumption that all sate variables of interconnected power system are available. However, in many interconnected power systems, the state variables are not accessible for direct measurement or the number of measuring devices is limited. In this paper, we propose an observer output-feedback load frequency control for interconnected power system, which the above limitation has been solved. The stability of both the observer error system and closed-loop control system is proven via the Lyapunov direct method. The proposed controller design is dependent on only the observer output. Therefore, the conservatism is reduced and the robustness is enhanced. It also both save computing time and make the control method simpler. Simulation results show that the proposed observer output-feedback load frequency controller results in shortening the frequency’s transient response,  maintaining required control quality in the wider operating range, and being more robust to uncertainties as compared to some existing control methods.